PELAKSANAAN AKAD TABARRU’ DAN AKAD WAKALAH BIL UJRAH PADA PRODUK ASURANSI SYARIAH DI AXA MANDIRI KCP BUAH BATU - Rahmat, Syaukani; Mubarok, Jaih (Al-Muamalat: Jurnal Ekonomi Syariah, 2019)
ABSTRACTMandiri Syariah Sejahtera Syariah is a product issued by one of the conventional insurance companies, namely AXA Mandiri, which is a sharia-based insurance product that has both the first benefit of the potential benefits of using tabarru 'contract and the second benefit is using the wakalah bil ujrah contract. The purpose of this study was to determine 1) the mechanism of implementation of tabarru 'contract in the Mandiri Sejahtera (MRS) product on Axa Mandiri at KCP Buah Batu Bandung 2) mechanism for the implementation of the wakalah bil ujrah contract in the Mandiri Rencana Sejahtera (MRS) product on Axa Mandiri on KCP Buah Batu Bandung 3) Assessment of Syari'ah Economic Law (Muamalah) on the implementation of tabarru 'contract and the contract of wakalah bil Ujrah in the Mandiri Sejahtera (MRS) product on Axa Mandiri at KCP Buah Batu Bandung. The conceptual framework or concept of problem solving in this study uses two DSN- MUI  fatwas,  first  Fatwa  No.53  /  DSN-MUI  /  III  /  2006  concerning  Tabarru. 'Agreement on Sharia Insurance and No.NDN. 52 / DSN-MUI / III / 2006 concerning the Wakalah Agreement on Uj Ujrah on Sharia Insurance and Sharia Reinsurance. The type of research used in this study is empirical research (socio legal research). Using descriptive analysis method, while the data collection method is through interviews, documentation and literature study, which is collecting, compiling, analyzing, managing data and drawing conclusions from this study. The conclusion obtained from this study is that 1) the implementation of the tabarru contract in which policyholders grant their funds to PT Axa Mandiri and are collected in separate accounts with other funds. 2) Implementation of the wakalah bil ujrah contract, where the customers represent PT Axa Mandiri to manage these funds in sharia instruments, divide the results when there is a surplus underwriting and perform Qardh (pinjman) in the event of a deficit. 3) As well as a review of Sharia Economic Law in the DSN fatwa No. 53 / DSN-MUI / III / 2006 concerning Tabarru 'Agreement on Sharia Insurance and No.NDN. 52 / DSN-MUI / III / 2006 concerning the Wakalah Agreement  Bil  Ujrah  on  Sharia  Insurance  and  Sharia  Reinsurance.  Against the implementation of the Tabarru 'Agreement and the Wakalah Bil ujrah contract in the Mandiri Renacana Sejahtera product in AXA Mandiri KCP Buahbatu is in accordance with Sharia Principles. But regarding the provisions of the contract not written down or clearly explained about the rights and obligations between the participants as participants in the group meaning. Where should be explained such as the rights andgations of participants as individuals so that there is clarity in the participants' understanding of the rights and obligations of the participants.